Quantifying Spillover Effects from Large Land-based Investment : The Case of Mozambique - Deininger, Klaus; Xia, Fang (Elsevier, 2016)
Almost a decade after a spike in land demand following the 2007–08 commodity boom, evidence on impacts of this phenomenon remains limited and mostly case study based. We show that information on location and start data of large farms, combined with existing smallholder farm surveys, allows to complement this with a difference-in-difference approach to systematically assess spillovers from large farm establishment. Illustrative application to Mozambique suggests positive short-term effects from newly established large farms on adoption of agricultural practices and input use by small farms less than 50 km from newly established large operations. Robustness checks for crop farms only also suggest job creation in the proximity of newly established crop, but not livestock farms. Yet, large farm establishment decreased perceived well-being within a 25-km band and, in the time horizon considered here, did not lead to better access to output markets, cultivation of larger areas or, once other factors are controlled for, higher yields. This allows us to reject the notion of negative spillovers from large farm establishment but casts doubt on the wisdom of large unconditional subsidies to attract investors. In addition to drawing policy conclusions for Mozambique, we highlight the methodology’s wider applicability and scope for expansion.